2022
DOI: 10.20525/ijrbs.v11i5.1849
|View full text |Cite
|
Sign up to set email alerts
|

The effect of logistics performance determinants on export performance

Abstract: From the mid-1980s, Morocco confirmed its choice to liberalize trade so that international trade could become a lever for development. However, despite these ambitions, the persistence of the trade deficit has led us to reflect on the challenges of exports and the factors that can trigger the emergence of new competition. At this level, logistics has become one of the key factors to circumvent the obstacles that affect the supply of Moroccan exports. This paper aims to study and assess the impact of the determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The outcome also runs counter to research that demonstrated that the impact of competitor orientation depends on a minimum level of CO (Grinstein, 2008), and CO is significant in organizational performance (Frösén et al , 2016; Pekovic and Rolland, 2012). Even if the rate of service to the customer is a common way to measure performance in logistics firms (Ait Lhassan et al , 2022), in international markets, levels of responsiveness to competitors better than the needs of foreign customers are getting more critical for emerging firms. This result contradicts the study of Tan and Sousa (2015) because the intensity of competition increases globally once the firm enters international markets.…”
Section: Discussionmentioning
confidence: 99%
“…The outcome also runs counter to research that demonstrated that the impact of competitor orientation depends on a minimum level of CO (Grinstein, 2008), and CO is significant in organizational performance (Frösén et al , 2016; Pekovic and Rolland, 2012). Even if the rate of service to the customer is a common way to measure performance in logistics firms (Ait Lhassan et al , 2022), in international markets, levels of responsiveness to competitors better than the needs of foreign customers are getting more critical for emerging firms. This result contradicts the study of Tan and Sousa (2015) because the intensity of competition increases globally once the firm enters international markets.…”
Section: Discussionmentioning
confidence: 99%